2020
DOI: 10.5114/wo.2020.97637
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk (un)awareness among women suffering from neurofibromatosis type 1 in Poland

Abstract: The main goal of this study was to draw the attention of physicians to commonly undisclosed risk of breast cancer (BrCa) in women suffering from neurofibromatosis type 1 (NF-1), which is 5-fold higher than in the general population. NF-1 related BrCa arises earlier (< 50 years) and is more advanced, with an increased mortality. NF-1 is one of the most frequent monogenic diseases worldwide and a tumor predisposition syndrome. The Nf1 gene is an important negative regulator of the Ras onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Literature data indicate that the most common genes for predisposition to breast carcinoma are: ATM, BARD1, BRCA1/2, CDH1, CHEK2, Nf1, PALB2, PTEN, RAD51C, RAD51D and TP53 [6]. A recent study confirmed the risk of breast cancer in women with neurofibroma type 1 (NF-1) [7]. As for the Nf1 gene, the so-called first hit mutation guaranteed that further carcinogenesis is inherited germinally in patients with NF-1 [8,9].…”
Section: Introductionmentioning
confidence: 97%
“…Literature data indicate that the most common genes for predisposition to breast carcinoma are: ATM, BARD1, BRCA1/2, CDH1, CHEK2, Nf1, PALB2, PTEN, RAD51C, RAD51D and TP53 [6]. A recent study confirmed the risk of breast cancer in women with neurofibroma type 1 (NF-1) [7]. As for the Nf1 gene, the so-called first hit mutation guaranteed that further carcinogenesis is inherited germinally in patients with NF-1 [8,9].…”
Section: Introductionmentioning
confidence: 97%
“…All the features of NF-1 listed above signi cantly complicate not only genetic counselling but the clinical diagnosis in early childhood as well. Contrary to toddlers, a correct clinical diagnosis of NF-1 based on phenotypic manifestations may be established in > 90% of children at the age of 6 years [10,11,12] (Table 1) and in adulthood. Although the diagnostic criteria allowing the accurate clinical diagnosis of NF-1 have been revised recently [13], the phenotypic presentation of the disease in adults is striking.…”
Section: Introductionmentioning
confidence: 99%